Hubungan Rasa Percaya Diri Dan Kemampuan Komumikasi Matematis Siswa Kelas IX MTS PP Darussalam - Okviani Syafti; Sefrinal; Kiahan Zakia (Algebra: Journal of Matematics, Statistics and Computation, 2025)
Mathematical communication skills are an important competence in mathematics learning, especially in the topic of Systems of Linear Equations in Two Variables, because students are required to express ideas, construct mathematical models, and explain solution steps systematically. However, these skills are still not optimal and are assumed to be related to affective factors, one of which is self-confidence. This study aimed to determine the relationship between students’ self-confidence and their mathematical communication skills among ninth-grade students of MTs PP Darussalam. This research employed a quantitative approach with a correlational design. The subjects of the study were 27 ninth-grade students selected using saturated sampling. Data were collected through a self-confidence questionnaire and a mathematical communication skills test. Data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test after meeting the assumptions of normality and linearity. The results showed that the average self-confidence score of the students was in the moderate category with a score of 52.56, while the average mathematical communication skill score was also in the moderate category with a score of 70.22. The Pearson correlation test indicated a significant positive relationship between self-confidence and mathematical communication skills, with a correlation coefficient of 0.62 and a significance value of 0.001. These findings imply that improving students’ self-confidence should be an important concern in mathematics learning because it can support the optimal development of students’ mathematical communication skills.